2016
DOI: 10.1016/j.jval.2016.08.108
|View full text |Cite
|
Sign up to set email alerts
|

Burden of osteoporosis-related hip fracture in asia. A review of health care costs and resource utilization

Abstract: The median hospital length of stay for all complication admissions was 3 days. ConClusions: Patients who develop fracture healing complications often have multiple admissions for treatment and incur high hospital inpatient costs. There is a need to prioritise future research aimed at preventing fracture healing complications and improving their management in order to reduce the additional burden placed on healthcare systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hip fracture will remain an important public health issue owing to the increasing burden placed on the healthcare system. 3 Previous studies estimate the 1-year mortality rate following a hip fracture to range from 10 to 40%, 4 7 and compared to the general population, the excess annual mortality remains higher for periods of up to 10 years. 8 However, a recent study in the Singapore population showed that absolute mortality following hip surgery decreased significantly by 21% in 2006 to 2011 and by 40% in 2012 to 2017 compared to 2000–2005.…”
Section: Introductionmentioning
confidence: 99%
“…Hip fracture will remain an important public health issue owing to the increasing burden placed on the healthcare system. 3 Previous studies estimate the 1-year mortality rate following a hip fracture to range from 10 to 40%, 4 7 and compared to the general population, the excess annual mortality remains higher for periods of up to 10 years. 8 However, a recent study in the Singapore population showed that absolute mortality following hip surgery decreased significantly by 21% in 2006 to 2011 and by 40% in 2012 to 2017 compared to 2000–2005.…”
Section: Introductionmentioning
confidence: 99%